Variabel Fundamental yang Mempengaruhi Struktur Keuangan dan Implikasinya terhadap Rentabilitas Ekonomi - Wiwiek Kusumaning Asmoro; Novie Astuti Setianingsih; Eti Putranti (Politeknik Ganesha Medan, 2021)
Fundamental variables in this research are shown in the level of sales growth, asset structure, company size and retained earnings. The purpose of this study was to determine the effect of sales growth rate, asset structure, firm size and retained earnings on financial structure. In addition, the purpose of this study is to examine how these variables affect economic rentability. The population in this study is the Food and Beverage Industry Sub-sector listed on the Indonesia Stock Exchange for the 2016-2020 period as many as 15 companies. The sampling technique is using purposive sampling which is a technique in sampling with certain considerations. The sampling technique is carried out proportionally sampling with the type of Judgment Sampling. Data collection technique used is documentation technique with polling data type. The number of samples in this study were 11 companies, the data used in the form of financial statements of the Food and Beverage Industry Subsector obtained from the Indonesia Stock Exchange. The results showed that sales growth and retained earnings had a positive effect on financial structure, while asset structure and firm size had a negative effect. The results of research on economic rentability, sales growth variables and retained earnings also have a positive effect, while asset structure and firm size have a negative effect. So the findings of this study can be concluded that the growth rate of sales, retained earnings can improve the financial structure and economic rentability of the company.